Adenosine deaminase polymorphism. Associations at clinical level suggest a role in cell functions and immune reactions. Issue 5 (October 1981) - Bottini, E; Carapella, E; Cataldi, L; Nicotra, M; Lucarelli, P; Lucarini, N; Pascone, R; Gloria-Bottini, F
Abstract : It is well known that subjects homozygous for a rare silent allele of ADA may experience a severe combined immunodeficiency. By analogy we have investigated the possible relationship of normal ADA polymorphism with some situations, such as reproductive defects and fetomaternal interactions, in which immunological mechanisms may play an important role. A total of 572 consecutive newborns, 93 consecutive low birthweight infants, 46 couples with unexplained habitual abortion, and 24 couples with unexplained sterility were studied. The proportion of ADA 2-1 phenotype was reduced in couples with reproductive defects. In the sample of consecutive newborns the proportion of ABO incompatible babies was higher among ADA 2-1 than among ADA 1 types. ADA 2-1 phenotype was also associated with a reduction in the variability of gestational length. These associations were much more marked among male than among female babies. The proportion of ADA 2-1 was significantly lower in low birthweight infants than in the consecutively studied infants and normal adults. The present data suggest that biochemical variability resulting from the normal ADA polymorphism may be, at least in part, responsible for the variability of some immunological functions and related physiological variables and pathological conditions. They also provide evidence in favour of a selective advantage of ADA heterozygotes.